Betty Jo Bewley: She Leads the Pigskin Parade (1946)
Text on back of photo reads: 'Betty Jo Bewley, wife of Lew Bewley, varsity grid player for the Cal Poly Mustangs, has the distinction of being the only girl to ever be a drum majorette at the non-coeducational agricultural and engineering college at San Luis Obispo. She was national baton twirling champion in 1940 and 1941, winning both years in competition held at Baylor University, Waco, Texas.' Betty Jo Bewley was married to student Lew Bewley. She served as the Cal Poly drum majorette from 1946 -1950.